2011
DOI: 10.1111/j.1600-0854.2011.01263.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacidification of Trans‐Golgi Network and Endo/Lysosomes in Melanocytes by Glucosylceramide‐Dependent V‐ATPase Activity

Abstract: Sphingolipids are considered to play a key role in protein sorting and membrane trafficking. In melanocytic cells, sorting of lysosomal and melanosomal proteins requires the sphingolipid glucosylceramide (GlcCer). This sorting information is located in the lumenal domain of melanosomal proteins. We found that two processes dependent on lumenal pH, protein sialylation and lysosomal acid lipase (LAL) activity were aberrant in GM95 melanocyte cells, which do not produce glycosphingolipids. Using fluorescence life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 62 publications
4
21
2
Order By: Relevance
“…By examining lysosomal markers LMP-1::GFP (Artal-Sanz et al, 2006; O’Rourke et al, 2009; Rabbitts et al, 2008), GLO-1::GFP (Schroeder et al, 2007; Zhang et al, 2010), and Neutral red (Long et al, 2002), we did not observe obvious defects in lysosome formation in elo-5(−) mutants (Figure 4—figure supplements 4 and 5). Major defects in lysosome formation would also be inconsistent with our genetic suppression data and previous studies on GlcCer by others (Entchev et al, 2008; van der Poel et al, 2011). One possible mechanism is that d17iso-GlcCer acts through the V-ATPase pathway, since the lysosomal V-ATPase has been shown to be stimulated by GlcCer and to play an essential role in TORC1 activation in studies using tissue culture cells (van der Poel et al, 2011; Zoncu et al, 2011; Bar-Peled et al, 2012).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…By examining lysosomal markers LMP-1::GFP (Artal-Sanz et al, 2006; O’Rourke et al, 2009; Rabbitts et al, 2008), GLO-1::GFP (Schroeder et al, 2007; Zhang et al, 2010), and Neutral red (Long et al, 2002), we did not observe obvious defects in lysosome formation in elo-5(−) mutants (Figure 4—figure supplements 4 and 5). Major defects in lysosome formation would also be inconsistent with our genetic suppression data and previous studies on GlcCer by others (Entchev et al, 2008; van der Poel et al, 2011). One possible mechanism is that d17iso-GlcCer acts through the V-ATPase pathway, since the lysosomal V-ATPase has been shown to be stimulated by GlcCer and to play an essential role in TORC1 activation in studies using tissue culture cells (van der Poel et al, 2011; Zoncu et al, 2011; Bar-Peled et al, 2012).…”
Section: Discussioncontrasting
confidence: 84%
“…Major defects in lysosome formation would also be inconsistent with our genetic suppression data and previous studies on GlcCer by others (Entchev et al, 2008; van der Poel et al, 2011). One possible mechanism is that d17iso-GlcCer acts through the V-ATPase pathway, since the lysosomal V-ATPase has been shown to be stimulated by GlcCer and to play an essential role in TORC1 activation in studies using tissue culture cells (van der Poel et al, 2011; Zoncu et al, 2011; Bar-Peled et al, 2012). Further biochemical and genetic analyses are needed to test this hypothesis in C. elegans .…”
Section: Discussioncontrasting
confidence: 84%
“…Other studies have corroborated genetically the importance of sphingolipids for V-ATPase function [83]. Moreover, luminal acidification of melanocyte trans-Golgi system and endo/lysosomes have been suggested to depend on glycosphingolipids, since a cell line devoid of glucosylceramide synthase presents defective luminal acidification [84]. Indeed, a regulatory function for lipid raft lipids in vivo can be envisaged: in a seminal study by Lafourcade et al [85] they observed that the V 1 /V 0 assembly ratio varies along the endocytic pathway in a way that correlates with the lipid-raft abundance and the luminal pH in these organelles.…”
Section: Structure Of V-atpasesmentioning
confidence: 89%
“…In Gaucher’s disease, the accumulation of cholesterol was associated with a secondary elevation in lysosomal pH (Sillence, 2013). Interestingly, reducing glucosylceramide synthase either chemically (Sillence, 2013) or molecularly (van der Poel et al, 2011) also alkalinized lysosomes, with the latter study suggesting glucosylceramide stimulates the vHATPase pump. This suggests that optimal levels of the protol pump require a balanced intermediate level of glucosylceramide.…”
Section: Chronic Retinal Degenerations Ion Transport Autophagy Amentioning
confidence: 91%